Arranging the street is the key to improving traffic safety - Osetrin, Mykola; Shilova, Tatiana (Transfer of innovative technologies, 2021)
The main purpose of the city's road network is to ensure fast, unobstructed and, most importantly, safe traffic for all its participants. This can be achieved both by rational planning of the street and road network of the city as a whole at the stage of the master plan, and by introducing various engineering measures for the arrangement of individual streets at the stage of a detailed plan of territories. Of course, each stage of urban planning has its own specifics and capabilities to ensure urban traffic, but all these measures should be developed as a single program, ranging from more generalized to the city as a whole and detailed for specific streets.